Wound healing activity of Helichrysum italicum essential oil-based ointment in diabetic rat model - Andjić, Marijana; Draginić , Nevena; Kočović, Aleksandar; Tomović, Marina; Petrović, Anica; Uštević, Andjela; Božin, Biljana; Kladar, Nebojša; Jakovljević, Vladimir; Bradić, Jovana (Archives of Pharmacy, 2022)
Helichrysum italicum is a typical Mediterranean plant belonging to the Asteraceae family. H. italicum essential oil, obtained by hydrodistillation from aerial flowering parts has been used traditionally for wound and burns treatment, but there is no scientific evidence that supports the traditional claim. The aim of our study was to estimate the antioxidant activity of commercial sample of H. italicum essential oil and investigate the wound healing effects of this essential oil-based ointment in diabetic rat. The antioxidant activity of essential oil was appraised by employing five in vitro test systems: 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay, hydroxyl ion (OH•), nitric oxide (NO•), lipid peroxidation (LP) and ferric reduction antioxidant potential (FRAP) test. Thirty-two diabetic rats with the induced excision wound were used to evaluate in vivo wound healing effects of ointment. The animals were randomly divided into four groups: untreated, topically treated with either a 1% silver sulfadiazine, the Eucerin base, or 0.5% essential oil ointment. The response to the treatment was assessed by macroscopic and biochemical analysis. Essential oil exhibited scavenging of DPPH. and .OH• radicals with IC50 values of 4.45±0.44 and 13.33±1.11 μg/mL, respectively. Furthermore, essential oil inhibited LP with IC50 = 10.48±1.22 mg/mL. Topical application of the H. italicum ointment showed the highest wound contraction from day 7 to day 21 with the highest content of hydroxyproline in comparison to the all examined groups. Our findings revealed that the H. italicum ointment approach might serve as a promising and innovative tool for wound healing.